CORRECTION OF EXOGENOUS RISK FACTORS FOR PERIODONTAL LESIONS IN PATIENTS WITH NON-ALCOHOLIC FATTY LIVER DISEASE AND THEIR SPOUSES - T.O. Petrushanko; D.V. Emelyanov (Український стоматологічний альманах, 2024)
Reduction of periodontal adaptive capacity to the constant action of exogenous factors occurs against the background of non-alcoholic fatty liver disease. Correction of such factors creates favorable conditions for the treatment and prevention of comorbid pathology. The study involved 44 married couples and 25 somatically healthy patients who were clinically examined by a dentist and a gastroenterologist, and questioned about their eating habits and oral care. It was determined that the most common habit among the subjects was the abuse of simple carbohydrates. In 88.6% of patients in the main group, inflammatory periodontal disease was diagnosed, the most common clinical form in 61.3% of patients was chronic generalized periodontitis of the second degree of severity, while in the observation group such pathology was detected in 43.1% of patients (13.6% had chronic catarrhal gingivitis, 20.4% had chronic generalized periodontitis of the first degree). After 12 months of implementation of treatment and prevention measures, there was a significant decrease in the presence of various combinations of habits in patients of both groups with positive dynamics of inflammatory diseases of periodontal tissues.